Opportunity identification and entrepreneurial behavior - Butler, John E., 1946- (Research in entrepreneurship and management., 2004)
Scholars of entrepreneurship provide a comprehensive view of opportunity identification, offer a number of theoretical extensions and developments, explore some new empirical territory, and suggest future research. Their topics include the enterprise-serving bias, behavior by different types of entrepreneurs, and how knowledge affects opportunity discovery and exploitation among new ventures in dynamic markets.